A polyoptimal catalogue of rolled profiles for a given class of spatial trusses - Badower, Aleksander; Paczkowski, Witold M.; Jendo, Stefan (Computer Assisted Methods in Engineering and Science, 2023)
The purpose of this polyoptimization was to find optimal tubular cross section catalogues for the specified spatial trusses. Five different spans of trusses have been analyzed, starting from 24 x 24 m ending at 72 x 72 m, trusses supported at every other perimeter node, with loading conditions typical for roofs. Four decision variables were taken under consideration, i.e. the catalogue size t, its arrangement T in a metallurgical catalogue TM , minimal and maximal diameters of tubular elements Dmin and Dmax. Two objective functions: truss mass and manufacturability of particular solutions were evaluated. For that purpose, some design, technological, and computational constraints were taken into account. For the specified spans L, different catalogues of cross sections were defined by TOPSIS method.